PEMAHAMAN MAHASISWA MENGENAI PELUANG USAHA JASA KONSULTAN PAJAK DAN FAKTOR-FAKTOR YANG MEMENGARUHINYA - Indriyarti, Eko Retno (Jurnal Pengabdian dan Kewirausahaan, 2018)
One character of self-reliance in relation to entrepreneurship is the taking of initiatives about the business opportunities that can result. Market opportunities indicate the need for more tax consultants in the effort of one of them achieving tax revenue targets. Efforts to increase these numbers can be supported early on starting from the level of Higher Education, where graduates with related courses can contribute in shaping the profession of tax consultants in Indonesia. The purpose of this study is to analyze whether the desire of career dipengaurhi by the basic factors. By using multiple regression analysis and measurement with SPSS, the results of the study explain that career choice is influenced by personal factors, intrinsic value of work, job market opportunity, financial reward, professional recognition, work environment, social value. Socialization of the profession as a consultant is deemed necessary especially to form and increase student motivation, especially from accounting study program. The study aims to know and analyze interest in marching as a tax consultant and the factors that influence it. The results of this study describe career choices as influenced by personalities, intrinsic value of employment, job market opportunities, financial rewards / awards, professional recognition, work environment, and social values. What and how career paths and job characteristics are deemed necessary to be delivered to students especially those from accounting study programs. It aims to motivate and interest in the profession semakian sharpened and directed with important information concerning this profession. Socialization by tax consultants to campuses is considered appropriate for the program to direct the potential of another company's career or independent business as a tax consultant.  Keywords: consultant, tax, profession, accounting